Remote monitoring technology and servitised strategies – factors characterising the organisational application - Grubic, Tonci; Jennions, Ian K. (Taylor and Francis, 2017)
This paper introduces factors that characterise the organisational application of remote monitoring technology (RMT) for servitised strategies. Factors were developed through in-depth case studies of four manufacturers operating in aerospace, industrial equipment, marine and transportation sector. They suggest a very complex, multi-levelled, multifaceted and circular relationship between RMT and servitisation. When unfolding this relationship we need to consider: the value proposition, nature of the product and its hierarchical position in the customer’s business, RMT functionality, type and amount of data required, and a number of other factors that either complement or constrain the use of RMT. By providing the necessary lenses, the proposed factors can help in exploring this complexity. One such exploration questions our understanding of outcome-based contracting.
Keywords: product service systems; technology management; remote monitoring technology; servitisation; strategies; factors